The history of African village chickens: An archaeological and molecular perspective - Mwacharo, Joram M.; Bjornstad, G.; Han Jianlin; Hanotte, Olivier H. (Springer, 2013)
The history of the introduction and dispersal of village chickens across the African continent is a subject of intense debate and speculation among scholars. Here, we synthesize and summarise the current scientific genetic and nongenetic knowledge in relation to the history of the species on the continent. Sociocultural, linguistic, archaeological and historic data all suggest a complex history for the species in Africa, characterized by multiple maritime and/or terrestrial introductions over time and several dispersal routes towards and within Africa. Molecular genetics information supports these observations and in addition suggests possible Asian centers of origin for African domestic chickens, including South Asia and Island Southeast Asia. However, both sets of data were until now too limited in their geographic scope, both within Africa and in comparison with chickens from Asia, to unravel the history of the species in detail. We anticipate that further continent-wide studies combining archaeological, ancient and/or modern genetic information may shed new insights on the history of the species. These will contribute to a deeper understanding of the history of trading networks and human interactions within Africa and between African and Asian societies, at the root of the development and expansion of African civilizations.